Analisis Keterampilan Membaca Permulaan dan Berhitung pada Siswa Sekolah Dasar - Murtafi'ah Murtafi'ah; Irfai Fathurohman; Himmatul Ulya (WASIS : Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine how the reading and numeracy skills possessed by elementary school students in grade 1 SD Kendalagung, RembangThe research approach used in this study is a qualitative approach (Qualitative Research). This research was conducted at SD Kendalagung, Rembang. The research informants were 6 grade 1 students at SD Kendalagung. Methods of data collection in this study using interviews, documentation, and field notes. The data analysis technique used is qualitative data which consists of data reduction, data presentation, and drawing conclusions.The results showed that the initial reading skills possessed by grade 1 students at SD Kendalagung were students able to voice pronunciation, students were able to understand the letters of the alphabet, students were able to read using appropriate intonation and fluency, students were able to read syllables, and students were able to understand word stops. . While the numeracy skills possessed by grade 1 SD Kendalagung students are students able to recognize numbers, students are able to sort numbers, students are able to count objects around, students are able to operate numbers (addition, subtraction, multiplication and division), and students are able to implement mathematical concepts in life daily.